2010
DOI: 10.1590/s1413-70542010000400019
|View full text |Cite
|
Sign up to set email alerts
|

Germinação e vigor de sementes de arroz inoculadas com bactérias diazotróficas

Abstract: RESUMOObjetivou-se, neste trabalho, avaliar a germinação e o vigor das sementes de arroz inoculadas com bactérias diazotróficas. Foram instalados dois experimentos, sendo que no primeiro o delineamento experimental adotado foi o inteiramente casualizado em esquema fatorial, com dois lotes de sementes arroz da cultivar IC4440 x 10 tratamentos, com quatro repetições. Os tratamentos foram representados pela inoculação com oito estirpes de bactérias diazotróficas (AR1122, M130, BF1358, ZAE94, AR3122, AR2112, CD e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
3
0
3
Order By: Relevance
“…N values in the flag leaf (leaf N) remained always in the range reported by Raij et al (2001) as adequate (27-35 g kg -1 ). Araújo et al (2010) and Goes (2012), evaluating Azospirillum brasilense inoculation in rice seeds, also did not find difference in the number of panicles per m 2 , corroborating the results found in the present study.…”
Section: Resultssupporting
confidence: 92%
“…N values in the flag leaf (leaf N) remained always in the range reported by Raij et al (2001) as adequate (27-35 g kg -1 ). Araújo et al (2010) and Goes (2012), evaluating Azospirillum brasilense inoculation in rice seeds, also did not find difference in the number of panicles per m 2 , corroborating the results found in the present study.…”
Section: Resultssupporting
confidence: 92%
“…Unlike in rice seeds, where it was observed that inoculation with strains of the genus Azospirillum gave a higher emergence speed and less contamination by fungi (ARAÚJO et al, 2010).…”
Section: Resultsmentioning
confidence: 90%
“…The remaining samples did not differ statistically from control seeds. Araújo et al (2010), when assessing the germination of rice seeds stored for one year and subsequently inoculated with strains of diazotrophic bacteria, found no positive effect of bacterial isolates, either. Dan et al (2010) also had no positive results for germination and first germination count of soybean seeds treated with thiamethoxam.…”
Section: Resultsmentioning
confidence: 91%